Reinterpreting Ridha in Fiqh Munakahat: A Maqasid al-Shariah Analysis of Child Grooming - Muhil Mubarok; Hawa’ Hidayatul Hikmiyah; A. Fikri Amiruddin Ihsan (The Indonesian Journal of Islamic Law and Civil Law, 2026)
This article examines whether ridha in fiqh munakahat can remain legally meaningful when a child's apparent assent is produced through grooming. The study departs from a doctrinal gap: classical fiqh generally discusses ridha in relation to coercion (ikrah), whereas child grooming operates through gradual psychological manipulation and unequal power relations. Using normative legal research with a conceptual and maqasid-based approach, this article analyzes classical discussions of ridha together with Jasser Auda's maqasid al-shariah, especially hifz al-nafs, hifz al-'aql, and hifz al-nasl. The article argues that a child's compliance in a grooming situation cannot be treated as valid ridha because it lacks psychological maturity, freedom from manipulation, and awareness of consequences. Its contribution lies in proposing a substantive formulation of ridha that moves beyond formal consent and functions as a doctrinal test for assessing exploitative relationships involving children. This reformulation strengthens the child-protective orientation of Islamic family law and clarifies the normative incompatibility between grooming and the objectives of sharia.